Diphyllobotrium Spp. as a cause of chronic diarrhea diagnosed only by colonoscopy or capsule endoscopy - Cedrón Cheng, Hugo Guillermo (2023)
We present two patients with chronic diarrhea, with multiple negative studies, both had in common vitamin B12 deficiency. Both patients had multiple studies of parasites in negative stool. Only after colonoscopy in the first case and capsule endoscopy in the second case, it was possible to diagnose the adult forms of Diphyllobotrium spp. After treatment, both patients completely resolved their symptoms.